2008
DOI: 10.2528/pierl07122804
|View full text |Cite
|
Sign up to set email alerts
|

Transmittance and Fractality in a Cantor-Like Multibarrier System

Abstract: Abstract-The transmittance is studied for a Cantor-like multibarrier system. The calculation are made in the framework of effective mass theory. Some typical values of effective masses and potentials are used in order to have an experimental reference. The techniques of Transfer Matrix are used to calculate the transmittance of the entire structure having some dozens of layers. The results display a complex structure of peaks and valleys. The set of maxima is studied with the tool of the q-dependent dimension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…2). The fundamentals of Schrödinger electrons can be found elsewhere, 30 and some minor details can be seen Fig. 3.…”
Section: Methodsmentioning
confidence: 99%
“…2). The fundamentals of Schrödinger electrons can be found elsewhere, 30 and some minor details can be seen Fig. 3.…”
Section: Methodsmentioning
confidence: 99%
“…They also show that the selfaffinity is a novel geometric property that is inherited to physical measurable properties of the model. It is worth mentioning that this scaling features in transmission had not been found, as far as we know, in non-relativistic systems for other kinds of systems [27][28][29].…”
Section: -P2mentioning
confidence: 92%
“…Several recent works have highlighted self-similar structures in graphene and reported self-similar behavior in transmission spectra and conductance. For instance, the Cantor-like multibarrier system was studied, and it was demonstrated that the set of transmittance maxima exhibits a fractal structure [24][25][26].…”
Section: Introductionmentioning
confidence: 99%